Group 2 ring-opening polymerisation catalysts - Unruangsri, J (2014)
This Thesis describes the synthesis and characterisation of new Group 2 tetrahydroborate, alkoxide and organohydroborate complexes and their uses as catalysts for the living ROP and immortal ring-opening polymerisation (iROP) of ε- caprolactone and rac-lactide. Chapter One introduces cyclic esters and possible mechanistic pathways leading to polyesters by ROP. Living and immortal ROP, including their kinetic characteristics are discussed. An overview of ROP from an industrial perspective is also given. Chapter Two describes the synthesis and characterisation of a new series of Group 2 tetrahydroborate complexes supported by a 3-methyl, 5-tert-butyl tris(pyrazolyl)hydroborate ligand. Their activities towards the ROP of ε-caprolactone are presented. Detailed mechanistic studies using spectroscopic techniques are discussed and a new mechanism is proposed. Chapter Three describes the ROP of rac-lactide using the Group 2 tetrahydroborate complexes introduced in Chapter Two, including their mechanistic studies. Chapter Four introduces the new immortal ROP using trialkyl borate and organoborane derivatives as chain-transfer agents (CTAs). The immortal ROP of ε- caprolactone and rac-lactide using Group 2 initiators with trialkyl borates/organoboranes as CTAs from either in situ generation or external addition is discussed. Possible immortal ROP pathways using this new class of CTAs are illustrated. Chapter Five details the synthesis and characterisation of a new series of Group 2 organohydroborate complexes. The ε-caprolactone and rac-lactide ROP activity shown by the complexes presented is discussed and compared with those obtained from the corresponding tetrahydroborate analogues. Chapter Six contains experimental details and characterising data for the new complexes reported in this Thesis. CD Appendix contains .CIF files for all the new crystallographically-characterised complexes.